Racial disparities in squamous cell carcinoma of the oral tongue among women: A SEER data analysis. Issue 6 (June 2015) - Joseph, Lindsay J.; Goodman, Michael; Higgins, Kristin; Pilai, Rathi; Ramalingam, Suresh S.; Magliocca, Kelly; Patel, Mihir R.; El-Deiry, Mark; Wadsworth, J. Trad; Owonikoko, Taofeek K.; Beitler, Jonathan J.; Khuri, Fadlo R.; et al.
Highlights Variations in incidence of OTC in women are described. Racial disparity in survival of women with OTC is pronounced. Incidences of OTC do not vary by residential area. White younger women experienced the sharpest increase in incidence. Further research to identify factors that may explain these changes is needed.